At the Limit of the Obscene : German Realism and the Disgrace of Matter - Weitzman, Erica (Book collections on Project MUSE., 2021)
"At the Limit of the Obscene: German Realism and the Disgrace of Matter examines the fear of materiality in German-language realist and postrealist literature"--